O8 A genome-wide association study of severe alcoholic hepatitis. (28th September 2020) - Sharma, Moksh; Atkinson, Stephen R; McQuillin, Andrew; Thursz, Mark R; Morgan, Marsha Y
Abstract : Introduction: Alcoholic liver disease (ALD) is a complex disorder, resulting from the interplay of environmental and genetic factors. Severe alcoholic hepatitis (AH) is an acute clinical manifestation of ALD, which has a high associated mortality but develops in only a minority of patients, estimated to be <15%. An understanding of the genetic factors underlying severe AH may be essential to improving risk-stratification and identifying novel therapeutic targets for this understudied syndrome. Methods: Cases with severe AH were recruited from the UK Steroids or Pentoxifylline for Alcoholic Hepatitis (STOPAH) trial (n = 812). Controls with a history of alcohol dependence but without evidence of significant liver injury were recruited from the Centre of Hepatology, Royal Free Hospital, London (n = 936). All participants were of white British/Irish descent. DNA was genotyped using two platforms Illumina HumanCoreExome BeadChip (Illumina, San Diego, USA) and Illumina PsychArray Beadchip (Illumina, San Diego, USA). Separate GWAS analyses were undertaken on each array using Plink v1.9 followed by meta-analysis in METAL. MAGMA gene and gene-set analyses were carried out using FUMA. Results: The variant rs738409 in PNPLA3 was associated with severe AH at genome-wide significance (PTHRESHOLD<5 × 10–8; P = 6.66 × 10–12; Z score = 6.865). Three additional independent risk loci were identified at the suggestive significance threshold, in ATP2C2 (ATPase Secretory Pathway Ca2+ Transporting 2), (PTHRESHOLD<1 × 10–5; PMETA = 4.33 × 10–7; Z score = 5.054), PHYH (Phytanoyl-CoA 2-Hydroxylase) (PMETA = 3.16 × 10–6; Z score = 4.66) and ANGPT1 (Angiopoietin 1) (PMETA = 5.12 × 10–6; Z score = -4.56). In addition, nine gene-sets were identified at statistical significance (PBON < 0.05) involving pathways associated with sterol regulatory element-binding protein signalling (PBON = 1.21 × 10–5), interleukin 17 secretion (PBON = 1.01 × 10–4) and regulation of natural killer T cell proliferation (PBON = 1.88 × 10–4). Conclusions: The pivotal role of PNPLA3:rs738409 in determining the risk for developing severe AH was confirmed in this study. In addition, potential risk loci were identified in ATP2C2, which encodes a Mn+/Ca2+ transporter and is highly expressed in the gastrointestinal tract; PHYH which is implicated in phytanic acid metabolism; phytanic acid binds to and/or activates the transcription factors PPAR-alpha and retinoid X receptor; and ANGPT1 which encodes the angiogenic promoter angiopoietin 1. Additionally, a number of potential pathways were identified, through gene set analysis, which appear to be involved in severe AH, influencing lipid metabolism and inflammation. These novel findings open new avenues for investigation and therapeutic endeavour.